2017
DOI: 10.1159/000469476
|View full text |Cite
|
Sign up to set email alerts
|

Leakage of Hepaticojejunal Anastomosis: Radiological Interventional Therapy

Abstract: Background: Hepaticojejunostomy is an established procedure accompanying liver resection as well as hepatobiliary and pancreatic surgery. Typical complications requiring radiological intervention are abscesses and anastomosis leakage. Biliary obstruction and strictures are less frequent indications for interventional radiology since many of them can be treated endoscopically. Methods: Depending on anatomic location, underlying etiology, and complication of leakage, different procedures of interventional radiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 8 publications
1
28
0
Order By: Relevance
“…Biliary leakage may originate from injury of the bile ducts, or from anastomotic leakage after bilio-enteric anastomosis. Literature shows an incidence from 2% to 10% after pancreatic surgery without iatrogenic biliary injury; if biliary injury occurred incidence may rise up to 24% ( Table 1) (1,3,4,(11)(12)(13)(14)(15). A multivariate analysis has shown that there are no independent risk factors to predict bile leakage (4).…”
Section: Review Articlementioning
confidence: 99%
See 3 more Smart Citations
“…Biliary leakage may originate from injury of the bile ducts, or from anastomotic leakage after bilio-enteric anastomosis. Literature shows an incidence from 2% to 10% after pancreatic surgery without iatrogenic biliary injury; if biliary injury occurred incidence may rise up to 24% ( Table 1) (1,3,4,(11)(12)(13)(14)(15). A multivariate analysis has shown that there are no independent risk factors to predict bile leakage (4).…”
Section: Review Articlementioning
confidence: 99%
“…Site of puncture should be as peripheral as possible because central puncture have higher risk for major vascular injury. The cholangiography is decision-making to plan treatment (11,17).…”
Section: Ptc and Ptbdmentioning
confidence: 99%
See 2 more Smart Citations
“…May and Hunold [3] report on rarely performed radiological interventions such as percutaneous transhepatic biliary drainage or stent in the case of anastomotic leakages of hepaticojejunal anastomoses.…”
mentioning
confidence: 99%